Seeing the Light, Hearing the Call: Women Religious as Spectators and Subjects of Popular Nun Films - Sabine, Maureen (The journal of religion and film, 2016)
Though popular films like The Bells of St. Mary’s (1945), Heaven Knows, Mr. Allison (1957), The Nun’s Story (1959), and The Sound of Music (1965) have routinely been criticized for circulating polarized stereotypes about nuns, convent memoirs indicate that some women felt the stirrings of a religious vocation from watching these movies. This article arose out of interest in whether other women heard God’s call through nun films, and is based on a survey of 86 sisters from 28 different communities who had entered the convent between 1947 and 2007, and were prepared to discuss what they saw in these popular films, how they responded to their stereotypes, and what religious meaning they found there.